Unlocking Students’ Success: Math Learning via Instagram Filter Innovations - Gusti, Valeria Yekti Kwasaning; Risnawati, Erna; Tanjung, Khoriyah Shofiyah (FKIP Universitas Lampung, 2024)
Unlocking Students’ Success: Math Learning via Instagram Filter Innovations Objectives: This study investigates the impact of Instagram-based filter learning media on junior high school students' learning outcomes in mathematics, focusing on relations and functions. Methods: Using a quantitative methodology, the study employed a one-group pretest-post-test design to measure learning outcomes before and after interventions. Data were analyzed using paired t-tests and Cohen’s d to assess both statistical and practical significance. Findings: The findings reveal that Instagram filters significantly improved students' mathematical understanding, with average scores increasing from 61,13 (pre-test) to 71,63 (post-test). The improvement was statistically significant (p < 0,05), with a large effect size (Cohen’s d = 1,02), indicating a substantial impact of the intervention. Furthermore, the use of Instagram filters enhanced engagement and motivation, helping students grasp abstract concepts more effectively. In terms of specific indicators, for Conceptual Understanding, the pretest score was 26,00, and the post-test score increased to 30,38. The N-Gain for this indicator was 31,25%, indicating a moderate improvement in students’ understanding of key concepts. For Procedural Knowledge, the pretest score was 24,00, and the post-test score increased to 27,75. The N-Gain for this indicator was 20,31%, showing low improvement in students’ ability to apply mathematical procedures. For Problem-Solving Skills, the pretest score was 10,25, and the post-test score increased to 13,50. The N-Gain for this indicator was 33.33%, reflecting moderate improvement in students’ ability to apply mathematical knowledge to solve real-world problems involving relations and functions. Conclusions: The results highlight Instagram's potential as an effective educational tool for mathematics. Instagram filters engage students while aligning with Indonesia's Merdeka Curriculum, promoting innovative, student-centered learning. This research offers valuable insights for educators looking to integrate interactive technologies into modern teaching methods. Keywords: instagram filter, mathematics learning media, relations and functions.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024128